PERKEMBANGAN EMBRIO DAN LARVA GURAMI (Osphronemus goramy Lac.) BASTAR, BLUESAFIR, DAN BULE - Dini W.K. Sari; Ign. Hardaningsih; Rustadi Rustadi (Jurnal Perikanan Universitas Gadjah Mada, 2004)
The objectives of this research were to know the diameter and hatching rate of eggs, development rate of embryos, and survival rate of larvae of three subspecies of giant gouramy. Design experiment used in this study was completely randomized design (CRD). Eggs were incubated at 290C and larvae were reared at the same temperature until post larvae stage (most of the yolk sac completely absorbed).The results showed that there was no significant difference among subspecies (a=5%). The average diameter of the eggs were 2.61, 2.47, and 2.39 mm for bule, bastar, and bluesafir, respectively. The highest hatching rate was reached by eggs of bluesafir, followed by bastar and bule. In addition, survival rates of larvae were 93.80%, 91.60%, and 84.20% for bule, bastar, and bluesafir, respectively. The highest specific length growth rate reached by bluesafir (7.4% per day) followed by bastar (6.80% per day) and bule (5.72% per day). The highest specific weight growth rate was reached by bule (6.85% per day) followed by bluesafir (6.65% per day) and bastar (5.37% per day).